Comparison of incidents of nausea and vomiting between general anesthesia With Endotracheal tube and spinal anesthesia in cesarean sections - Mojgan Rahimi; Hussein Majedi; Afzal Shamsi; Negar Eftekhar; Rawaa Ali Kadhim (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: Nausea refers to a sense of vomiting inclination, while Vomiting refers to reflux of the gastric contents, it is multidimensional phenomena influenced by a variety of risk factors began during the operation and persisted in the recovery period. Postoperative phase results in decreased patient comfort, an extended stay in the PACU. Aim: To determine and compare which type of anesthesia leading to higher incidence of nausea and vomiting.Patients & Methods: (110) patients of 18-40 years with ASA I and II were assigned according to the type of anesthesia that will be used. The two groups of study (general and spinal anesthesia) each group contain 55 participants. Within the groups 28 of parturient received metoclopramide while the other 27 women were received ondansetron. Measuring times of episodes of intra-postoperative NV, time of recovery, hemodynamic parameters before and after incidents of NV, times of drug administration. Data analysis done by SPSS version 24. Results: times of episodes of NV was significantly less in spinal anesthesia group compared to general group (p